Análise de relações fator-produto na cultura do milho em Jardinópolis e Guaíra, Estado de São Paulo, ano agrícola 1969/70 - Biserra, José Valdeci (1971)
The main objective of this study was to estimate a corn production function for the "município" (county) of Jardinópolis and another for the "municipio" of Guaira.From these functions, the following specific objectives were pursued: (1) to estimate the average and marginal productivities of productive resources utilized in corn production; (2) to determine the returns to scale; (3) to estimate the "optimum" allocation of conventional inputs under the price tens prevailing at the time of the study; (4) to estimate the marginal rate of substitution between production factors; (5) to make an economic interpretation of the results in order to explore the possibilities of change; (6) to estimate the contribution of the farmer formal education and of the rural extension activities to production. The basic information analized in this study was obtained through direct interviews with farmers of a randon sample taken from a list of farmers registered at INCRA in the "municipios" of Jardinópolis and Guaíra. The sample was composed of 74 observations in the "municipio" of Jardinopólis and 80 in Guaira, relative to the agricultural year 1969/70. However, in view of the inconsistency of the information contained in some of the questionnaires and also the fact that some of the farmers did not grow corn on a commercial scale, the research was based on 60 observations for Jardinópolis and 64 for Guaíra. In order to estimate the production functions which "best" represent the factor-product relationships and were adapted to the objectives of the study, twenty seven equations were tested separately, six of which with the linear model and twenty-one with the Cobb-Douglas model. Thirteen of the equations tested with the latter model, were for the "município" of Jardinópolis and eight for the "município" of Guaíra. The choice of the "best" equations was based on the following criteria: (a) consistency of the results with the principles which rule the production relationships; (b) statistical significance of the regression coefficients; (c) value of the correlation coefficients between independent variables; (d) magnitude of the multiple determination coefficient. The adjustment of the estimate equations was made by the method of least squares and the electronic computation of the original statistical data was made at the "Centro de Computação Eletrônica" of the "Escola Superior de Agricultura "Luiz de Queiroz". Two of the specific objectives of the study, that is, estimation of marginal rates of substitution between factors and the deter mination of the "optimum" level could not be reached in view of the inference referring to the complementarily among factors. Because of the problem of multicolinearity two equations were selected for each "município".